Electrical Properties of Photodiode Ba0.25Sr0.75TiO3 (BST) Thin Film Doped with Ferric Oxide on p-type Si (100) Substrate using Chemical Solution Deposition Method - Irzaman Irzaman; H. Syafutra; H. Darmasetiawan; H. Hardhienata; R. Erviansyah; F. Huriawati; Akhiruddin Akhiruddin; M. Hikam; P. Arifin (Atom Indonesia, 2011)
In this paper we have grown pure Ba0.25Sr0.75TiO3 (BST) and BST doped by Ferric Oxide Fe2O3 (BFST) with doping variations of 5%, 10%, and 15% above type-p Silicon (100) substrate using the chemical solution deposition (CSD) method with spin coating technique at rotation speed of 3000 rpm, for 30 seconds. BST thin film are made with a concentration of 1 M 2-methoxyethanol and annealing temperature of 850oC for the Si (100) substrate. Characterization of the thin film is performed for the electrical properties such as the current-voltage (I-V) curve using Keithley model 2400 as well as dielectric constant, time constant, pyroelectric characteristics, and depth measurement. The results show that the thin film depth increases if the concentration of the Ferric Oxide doping increases. The I-V characterization shows that the BST and BFST thin film has photodiode properties. The dielectric constant increases with the addition of doping. The maximum dielectric constant value is obtained for 15 % doping concentration namely 83.1 for pure BST and 6.89, 11.1, 41.63 and 83.1, respectively for the Ferric Oxide doping based BST with concentration of 5%, 10%, and 15%. XRD spectra of 15% of ferric oxide doped BST thin film tetragonal phase, we carried out the lattice constant were a = b = 4.203 Å; c = 4.214 Å; c/a ratio = 1.003. Received: 01 February 2010; Revised: 04 October 2011; Accepted: 02 November 2011